Real-world clinical outcomes with avelumab in patients with Merkel cell carcinoma treated in the USA: a multicenter chart review study. Issue 8 (18th August 2022) - Bhatia, Shailender; Nghiem, Paul; Veeranki, S Phani; Vanegas, Alejandro; Lachance, Kristina; Tachiki, Lisa; Chiu, Kevin; Boller, Emily; Bharmal, Murtuza
Abstract : Background: Merkel cell carcinoma (MCC) is a rare, aggressive, cutaneous neuroendocrine neoplasm with annual incidence rates of 0.13–1.6 cases/100, 000/year worldwide as of 2018. Chemotherapy for metastatic MCC (mMCC) has high objective response rates (ORRs), but responses are not durable and overall survival (OS) is poor. Avelumab (anti-programmed death-ligand 1) has demonstrated meaningful survival benefit and durable responses in clinical trials for mMCC. This study investigated real-world clinical outcomes in avelumab-treated patients with advanced (stage IIIB/IV) MCC in US academic medical centers. Methods: We conducted a retrospective chart review of patients with advanced MCC who initiated avelumab between March 1, 2017, and July 31, 2019, at six US academic centers. Data were requested for eligible patients from index date through December 31, 2020. Descriptive analyses were conducted to assess demographic and clinical characteristics, real-world ORR (rwORR), real-world duration of response, real-world progression-free survival (rwPFS), and OS. Results: Ninety patients with advanced MCC (82%, stage IV; 18%, stage IIIB) received avelumab. Median follow-up was 20.8 months (95% CI: 19.1 to 24.2). Median age was 68 years (range, 48–83), and the majority of patients were men (58%) and white (93%). The primary tumor was most commonly located on the lower limb (38%), with metastases mostly located in lymph nodes (68%), lung (52%), and viscera (52%). Approximately 42% and 26% of patients had an Eastern Cooperative Oncology Group performance status of 2 and 3, respectively. Seventy-three patients (81%) received avelumab as first-line treatment of advanced MCC, while 17 (19%) received avelumab as second-line or later treatment. The median duration of avelumab treatment was 13.5 months (95% CI: 6.4 to 30.6), with 42% of patients still receiving avelumab by the end of follow-up. Patients with avelumab treatment had an rwORR of 73% (95% CI: 64 to 83), median rwPFS of 24.4 months (95% CI: 8.31 to not estimable (NE)), and median OS of 30.7 months (95% CI: 11.2 to NE). Conclusions: This real-world study of patients with advanced MCC demonstrated that avelumab treatment resulted in a high response rate with durable responses and prolonged survival. The study findings validate the results demonstrated in prospective clinical trials and other observational studies.